Visual Complexity A Review. [article]. - Donderi, Don C.
The idea of visual complexity, the history of its measurement, and its implications for behavior are reviewed, starting with structuralism and Gestalt psychology at the beginning of the 20th century and ending with visual complexity theory, perceptual learning theory, and neural circuit theory at the beginning of the 21st century. Evidence is drawn from rsearch on single forms, form and texture arrays and visual displays. Form complexity and form probability are shown to be linked through their reciprocal relationship in complexity theory, which is in turn shown to be consistent with recent developments in perceptual learning and neural circuit theory. Directions for further research are suggested. -- (from the author)